2002
DOI: 10.1017/s0266466602183046
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Variable Interpretation of Cointegration With Inference Results for Fractional Cointegration

Abstract: In this paper we propose an alternative characterization of the central notion of cointegration, exploiting the relationship between the autocovariance and the crosscovariance functions of the series+ This characterization leads us to propose a new estimator of the cointegrating parameter based on the instrumental variables~IV! methodology+ The instrument is a delayed regressor obtained from the conditional bivariate system of nonstationary fractionally integrated processes with a weakly stationary error corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The Monte Carlo simulation results given in Kitamura and Phillips () also show that the kernel estimates of the probability density functions of the crude IV and the FM‐IV estimators both become more dispersed than the OLS estimator when the I(1) instrument becomes less relevant. This observation provides intuitive support for the choice of lagged integrated covariates of Marmol et al () as I(1) IVs, based on which Marmol et al () proposed another FM‐IV estimator. Theoretically, Marmol et al () showed that their FM‐IV estimator is asymptotically equivalent to the FM‐OLS estimator.…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…The Monte Carlo simulation results given in Kitamura and Phillips () also show that the kernel estimates of the probability density functions of the crude IV and the FM‐IV estimators both become more dispersed than the OLS estimator when the I(1) instrument becomes less relevant. This observation provides intuitive support for the choice of lagged integrated covariates of Marmol et al () as I(1) IVs, based on which Marmol et al () proposed another FM‐IV estimator. Theoretically, Marmol et al () showed that their FM‐IV estimator is asymptotically equivalent to the FM‐OLS estimator.…”
Section: Introductionsupporting
confidence: 55%
“…This observation provides intuitive support for the choice of lagged integrated covariates of Marmol et al () as I(1) IVs, based on which Marmol et al () proposed another FM‐IV estimator. Theoretically, Marmol et al () showed that their FM‐IV estimator is asymptotically equivalent to the FM‐OLS estimator. For the rest of the article, the FM‐IV estimator is referred to as the FM‐IV estimator of Marmol et al ().…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Johansen (1992) considers the efficiency of the one-step maximum likelihood estimation procedure of linear EC models based on weakly exogenous variables. On the other hand, Phillips and Hansen (1990), Phillips (1991), Phillips and Loretan (1991), and Marmol et al (2002) study alternative efficient least-squares and instrumental variables estimators, always within a linear cointegration context.…”
Section: Introductionmentioning
confidence: 99%
“…IV estimation has previously been considered in a cointegration context, mostly in the traditional case of I (1) observables and I (0) cointegrating errors, but typically to provide representations of optimal estimates, that may also have an approximate maximum likelihood interpretation, say (see e.g. Phillips and Hansen 1990; Kitamura and Phillips 1995, 1997; Marmol et al 2002).…”
Section: Introductionmentioning
confidence: 99%